Analisis Tingkat Efisiensi dan Produktivitas Perbankan di Indonesia Ketika dan Setelah Pandemi Covid 19 - Ninda Ardiani; Nur Latifah, Fitri; Oktaviyanti, Ika; Aura Salsabil, Jasmine (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2024)
This study attempts to ascertain the productivity and efficiency levels of eight Islamic banks and eight conventional banks in Indonesia during and after the COVID-19 pandemic. Using Data Envelopment Analysis (DEA) and Malmquist's Productivity Index (MPI), this study's input factors include labor expenses, assets, financing and revenue, and Third Party Funds (DPK). The findings indicate that the highest degree of efficiency has been effectively maintained by Bank Mandiri, BTN, BTPN, KB Bank Syariah, and BVS. Following the Covid-19 epidemic, BNI was the only bank to see an derivation in performance. Potential improvements in labor cost and revenue management were identified in a number of institutions by the Total Potential Improvement analysis .However, the MPI investigation demonstrates that banks such as BTPN and MEGA have seen notable boosts in productivity due to their successful adoption of digital technology. All things considered, this study demonstrates how the COVID-19 pandemic has affected Indonesian banks' performance. While some banks have maintained or even increased productivity, banks still face substantial hurdles in terms of profitability and efficiency. These findings suggest that in order to meet upcoming difficulties, operational efficiency gains and technology breakthroughs are essential.